2023
DOI: 10.1111/1759-7714.14794
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0043256 upregulates KLF2 expression by absorbing miR‐1206 to suppress the tumorigenesis of lung cancer

Abstract: Background Circular RNAs (circRNAs) have been reported to play roles in lung cancer development. The purpose of this work was to explore the function and mechanism of circ_0043256 in lung cancer tumorigenesis. Methods Quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot were used for the detection of the levels of genes and proteins. Cell growth, angiogenesis ability, migration, and invasion were analyzed by using 5‐ethynyl‐2′‐deoxyuridine (EdU) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Additionally, in the A549 and PC9 lung cancer cell lines, miR-1206 expression was greater than that in their noncancerous counterparts [31]. Inhibition of miR-1206 suppressed cell proliferation, blood vessel formation, migration, and invasion but increased apoptosis in A549 and PC9 lung cancer cell lines [31,38]. We observed a prominent reduction in the proliferation and invasion of OVCAR3CIS cells upon miR-1206 knockdown, and its reduced expression correlates well with ovarian cancer patient outcomes.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Additionally, in the A549 and PC9 lung cancer cell lines, miR-1206 expression was greater than that in their noncancerous counterparts [31]. Inhibition of miR-1206 suppressed cell proliferation, blood vessel formation, migration, and invasion but increased apoptosis in A549 and PC9 lung cancer cell lines [31,38]. We observed a prominent reduction in the proliferation and invasion of OVCAR3CIS cells upon miR-1206 knockdown, and its reduced expression correlates well with ovarian cancer patient outcomes.…”
Section: Discussionmentioning
confidence: 66%
“…Gutierrez-Camino et al showed that miR-1206 is a potential biomarker for predicting methotrexate toxicity during chemotherapy treatment in pediatric acute lymphoblastic leukemia patients [30]. qRT-PCR of 36 pairs of tumor tissues and adjacent tissues collected from lung cancer patients revealed increased miR-1206 expression in the cancerous tissues [31]. Additionally, in the A549 and PC9 lung cancer cell lines, miR-1206 expression was greater than that in their noncancerous counterparts [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al revealed that ZNRD1-AS1 upregulation increased tensin 1 levels by sponging miR-942, thereby suppressing LC angiogenesis (137). In addition, circ_0043256 upregulation remarkably repressed angiogenesis in LC cells by upregulating KLF2 via absorbing miR-1206 (138). In-depth investigations are needed to further clarify the ncRNA action in angiogenesis, which may bring significant advantage for the development of theoretical basis in LC treatment.…”
Section: Ncrna In Lc Angiogenesismentioning
confidence: 99%